TINGKAT KEPUASAN PASIEN DALAM PELAYANAN KEFARMASIAN DI RUMAH SAKIT: SEBUAH NARRATIVE LITERATURE REVIEW - Reihana, Elza; Wahyuningsih, Sri (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study was to analyze the level of patient satisfaction in pharmaceutical services in hospitals. The research method used is a literature study or literature review with a narrative study approach from several accredited journals and articles that meet the screening criteria. This literature study was conducted through a search for scientific publications between 2018-2023 using the google schollar website, sage pub journal, and international journal websites. A total of 15 national and international journals matched the criteria and themes discussed in the literature review. The results found from this research are that the positive experience experienced by patients when visiting or seeking treatment will influence the level of patient satisfaction in pharmaceutical services.